2018
DOI: 10.1038/s41467-018-07335-2
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity of soil giant viruses

Abstract: Known giant virus diversity is currently skewed towards viruses isolated from aquatic environments and cultivated in the laboratory. Here, we employ cultivation-independent metagenomics and mini-metagenomics on soils from the Harvard Forest, leading to the discovery of 16 novel giant viruses, chiefly recovered by mini-metagenomics. The candidate viruses greatly expand phylogenetic diversity of known giant viruses and either represented novel lineages or are affiliated with klosneuviruses, Cafeteria roenbergens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
143
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 74 publications
2
143
1
1
Order By: Relevance
“…3A) and microbial sequences resulted in a more expansive range of putative host organisms associated with viruses. Only a small fraction of viral contigs had significant associations with specific microorganisms (440 of 19,094 contigs in the rarefied table; 2.3%), although many viral contigs (18,567) and microbial OTUs (12,512 of 21,895) were present at less than three locations and therefore excluded from our network (see methods). In the co-occurrence network, four viral contigs (0.9%) also had hosts identified by sequence homology, consistent with the proportion of sequence-identified hosts in the full dataset (0.8%).…”
Section: Microbial Hosts For Soil Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…3A) and microbial sequences resulted in a more expansive range of putative host organisms associated with viruses. Only a small fraction of viral contigs had significant associations with specific microorganisms (440 of 19,094 contigs in the rarefied table; 2.3%), although many viral contigs (18,567) and microbial OTUs (12,512 of 21,895) were present at less than three locations and therefore excluded from our network (see methods). In the co-occurrence network, four viral contigs (0.9%) also had hosts identified by sequence homology, consistent with the proportion of sequence-identified hosts in the full dataset (0.8%).…”
Section: Microbial Hosts For Soil Virusesmentioning
confidence: 99%
“…Eukaryotic viruses with large genomes typically spanning several megabases have been identified in aquatic systems 24,25 and, more recently, in terrestrial ecosystems, including soils 18,26,27 . Schulz et al 18 uncovered 16 novel giant virus genomes from metagenomes of forest soils and indicated that their discoveries constituted only a small fraction of the heretofore unknown giant virus diversity of soils. Here, we identified 1,676 putative giant virus sequences containing hallmark protein families of major capsids in NCLDV viruses ( Supplementary Table 4).…”
Section: Viral Abundance and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is in stark contrast to genomes of large and giant viruses of the NCLDV, which can be up to several megabases (Abergel et al, 2015;Fischer, 2016) . Importantly, recent studies showed that these viruses are among the most diverse and abundant entities in marine systems (Hingamp et al, 2013;Mihara et al, 2018) and are also found in a wide range of non-marine ecosystems (Graham et al, 2019;Kerepesi and Grolmusz, 2017;Roux et al, 2017;Schulz et al, 2018Schulz et al, , 2017bVavourakis et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of a giant virus genome from a wastewater treatment plant strongly supports the hypothesis that giant viruses evolved from smaller viruses by taking up bits and pieces of DNA from their hosts . More recent metagenome studies further show that the currently assessed diversity of giant viruses is likely a vast underestimate (Schulz et al, 2018;Mihara et al, 2018).…”
mentioning
confidence: 99%